2013
DOI: 10.1590/s0103-21002013000500005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da profilaxia no primeiro atendimento pós-exposição ao vírus da raiva

Abstract: Objective: To evaluate primary care prophylactic post-exposure anti-rabies treatment.Methods: This was a cross-sectional, descriptive and analytical study, with data from the Information System for Notification of Diseases. It analyzed 39,087 visits, excluding 1,091 (2.79%) cases of re-exposure and pre-exposure, resulting in 37,996 post-exposure visits. A logistic regression analysis was performed for adjustment of the treatment. Results: A predominance of Caucasians (83.93%), male (54.58%), primary school edu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
0
2
0
10
Order By: Relevance
“…Os estudos realizados no Brasil quanto à inadequação da conduta antirrábica apontaram taxas variando entre 3,8% a 24,7% (Frias et al, 2011). No Brasil, Veloso et al, (2011), encontraram 41,9% dos atendimentos adequados; Busatto et al, (2014), identificou 75,2% dos atendimentos com conduta adequada; Moriwaki et al, (2013) Quanto aos atendimentos que receberam tratamento em excesso, a principal conduta foi vacina 634 (21,1%). As condutas em excesso mais significativas foram: (0,6%) atendimentos receberam vacina e era para ser prescrito dispensa de tratamento, conforme protocolo do Ministério da Saúde, refletindo assim, sobre o risco de eventos adversos vacinais, aumento dos gastos públicos com a administração de vacinas, e recursos humanos da área de saúde.…”
Section: Resultsunclassified
“…Os estudos realizados no Brasil quanto à inadequação da conduta antirrábica apontaram taxas variando entre 3,8% a 24,7% (Frias et al, 2011). No Brasil, Veloso et al, (2011), encontraram 41,9% dos atendimentos adequados; Busatto et al, (2014), identificou 75,2% dos atendimentos com conduta adequada; Moriwaki et al, (2013) Quanto aos atendimentos que receberam tratamento em excesso, a principal conduta foi vacina 634 (21,1%). As condutas em excesso mais significativas foram: (0,6%) atendimentos receberam vacina e era para ser prescrito dispensa de tratamento, conforme protocolo do Ministério da Saúde, refletindo assim, sobre o risco de eventos adversos vacinais, aumento dos gastos públicos com a administração de vacinas, e recursos humanos da área de saúde.…”
Section: Resultsunclassified
“…Previous studies have performed descriptive analysis to summarize the SINAN database at national and state level [18–21], but the accuracy of the SINAN database as a tool for the surveillance of rabies and for the appropriate use of PEP has not been evaluated. In Brazil, dog bite incidence was high between 2002 and 2009 with 425 000 bites estimated per year [19,22]. The reduction of canine rabies cases over the last decade in Brazil should cause a concommittant decline in bites from rabid dogs and potential savings in PEP administration, but this has not been realized.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the procedures adopted by the health service and those recommended by the Ministry of Health, it was observed that the behaviors excessively adopted by the health service represented 10.3%, while 18.6% were classified as insufficient (Table 3). Moriwaki et al (2013) observed that 13.4% of the conducts were excessive and 28.1% were insufficient; Fernandes (2013) found that 16% of the procedures were insufficient and 7% were excessive; Cabral et al (2018) observed that 21.2% of the conducts were excessive and 11.5% were insufficient.…”
Section: Resultsmentioning
confidence: 99%